When research disciplines come together for greater impact - Dalsgaard, Jens Peter T. (International Livestock Research Institute, 2016)
The mentoring of “gender fellows” – younger scientists in more technical disciplines such as fish feeds or genetics – is an interesting, novel initiative. Gender mainstreaming in research will take time – perhaps longer than anticipated. It will require sustained interventions and follow-up, for example through ongoing mentoring. Gender research has an important contribution to make as a discipline in its own right, and can promote inter-disciplinarity to make research more development-relevant and impactful. Gender research is essential to our mission; it is not about women only, but about analysing the roles of men and women, producing more equity and benefit for all. Interview with Jens Peter Tang Dalsgaard (WorldFish) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568